From family to families: pushing family entrepreneurship forward. Issue 5 (27th May 2021) - Randerson, Kathleen; Frank, Hermann; Dibrell, Clay; Memili, Esra
ABSTRACT: The present guest editorial offers a review of the different conceptualizations of families in business used in research to date, shedding light on the unique characteristics of each type. Understanding the family through the lens of social systems theory offers a means for researchers to study contextually embedded family systems, offering a foundation for studying differences among families. We demonstrate that the family business system (ownership, business, family) is incomplete without a fourth component, that of the family in business. We then present the papers included in this special issue and highlight the collective contribution to research in the fields of family business and family entrepreneurship and provide directions for future research.